2001
DOI: 10.1034/j.1600-0412.2001.800115.x
|View full text |Cite
|
Sign up to set email alerts
|

Homologous intrauterine insemination. An evaluation of prognostic factors based on a review of 2473 cycles

Abstract: IUI-H is a simple and inexpensive treatment giving acceptable pregnancy rates for up to four treatment cycles providing that at least 3 to 4 mature follicles have developed at the time of insemination, which implies that hormonal ovarian stimulation and induction of ovulation is used, that insemination occurs between cycle day 13 and 16 and that at least 5 million motile sperms are available for insemination. Our results indicate that in the presence of tubal pathology or less than 5 million motile sperms, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
53
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 36 publications
12
53
2
Order By: Relevance
“…All these studies were retrospective except one [21], which was a prospective observational study and included 1,624 couples who underwent 3,381 clomiphene citrate-stimulated IUI cycles using either husband or donor sperm. The results of our study as well as those of others [2,6,7] showed that most of the pregnancies occurred in the first four treatment cycles, although few patients received more than 4 cycles. Other authors found that SIUI has the highest pregnancy rate within the first two [20,21,23] or three [1,[3][4][5]8] treatment cycles.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…All these studies were retrospective except one [21], which was a prospective observational study and included 1,624 couples who underwent 3,381 clomiphene citrate-stimulated IUI cycles using either husband or donor sperm. The results of our study as well as those of others [2,6,7] showed that most of the pregnancies occurred in the first four treatment cycles, although few patients received more than 4 cycles. Other authors found that SIUI has the highest pregnancy rate within the first two [20,21,23] or three [1,[3][4][5]8] treatment cycles.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have evaluated some or all of the prognostic factors influencing the success rate of IUI including the age of the woman [2], the sperm count and quality [4,20,21] or combined factors including the cycle's number [1,3,5,7,10,22,23]. All these studies were retrospective except one [21], which was a prospective observational study and included 1,624 couples who underwent 3,381 clomiphene citrate-stimulated IUI cycles using either husband or donor sperm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When it came to male factor consideration, attaining 5 million motile sperm threshold for IUI is recommended [21,28], while there is no consensus on a lower limit of semen quality at which one would advocate IUI [29];the systematic review confirms favourable correlation with IUI success in the range of 5-10 million [30].…”
Section: Discussionmentioning
confidence: 99%
“…It must be remembered that Total Motile Sperm Count [TMSC] inseminated has been cited as the most predictive index of conception after IUI cycles [9][10][11]. A minimalTMSC of 1 million for insemination was initially reported to be a requirement for pregnancy after insemination [12], but the systematic review of the literature by Ombelet et al in 2014 indeed confirms that the native sperm TMSC which shows the best correlation with IUI success is in the range of 5-10 million [6,[13][14][15][16]. According to a previous study, sperm concentration above 10 million is not related to further improvement in conception rates [12], while other investigators have reported the best pregnancy rates when more than 10 million motile spermatozoa are inseminated [9,17].…”
Section: Influence Of Semen Qualitymentioning
confidence: 99%